Renal Tissue-Derived Exosomal miRNA-34a in Diabetic Nephropathy Induces Renal Tubular Cell Fibrosis by Promoting the Polarization of M1 Macrophages - Shuai Zheng; Yi Zeng; Liqing Chu; Taiyang Gong; Sihong Li; Min Yang (IET Nanobiotechnology)
Background. Diabetic nephropathy (DN) is the leading cause of chronic kidney disease, and the activation and infiltration of phagocytes are critical steps of DN. This study aimed to explore the mechanism of exosomes in macrophages and diabetes nephropathy and the role of miRNA-34a, which might provide a new path for treating DN. Materials and Methods. The DN model was established, and the success of the model establishment was confirmed by detecting general indicators, HE staining, and immunohistochemistry. Electron microscopy and NanoSight Tracking Analysis (NTA) were used to see the morphology and size of exosomes. MiRNA-34a inhibitor, miRNA-34a mimics, pc-PPARGC1A, and controls were transfected in macrophages with or without kidney exosomal. A dual-luciferase reporter gene experiment verifies the targeting relationship between miRNA-34a and PPARGC1A. After exosomal culture, macrophages are co-cultured with normal renal tubular cells to detect renal tubular cell fibrosis. Q-PCR and western blot were undertaken to detect related RNA and proteins. Results. An animal model of diabetic nephropathy was successfully constructed. Macrophages could phagocytose exosomes. After ingesting model exosomes, M1 macrophages were activated, while M2 macrophages were weakened, indicating the model mice’s kidney exosomes caused the polarization. MiRNA-34a inhibitor increased PPARGC1A expression. MiRNA-34a expressed higher in diabetic nephropathy Model-Exo. MiRNA-34a negatively regulated PPARGC1A. PPARGC1A rescued macrophage polarization and renal tubular cell fibrosis. Conclusion. Exosomal miRNA-34a of tubular epithelial cells promoted M1 macrophage activation in diabetic nephropathy via negatively regulating PPARGC1A expression, which may provide a new direction for further exploration of DN treatment.